A model of university financial performance. (2nd November 2004) - Pursglove, Jeff; Simpson, Mike
University financial performance presents a complex set of problems for managers. This research provides a simple pyramid of financial performance and resultant ratios, developed solely from data to be found in the public domain. These ratios describe the nature of a university's business, its academic and operational efficiency and its research strategy. In addition to highlighting the characteristics of individual universities, the production of matrices from these ratios shows how alliances of universities differ from one another and allows the financial effects of strategic direction to be mapped over time.